Aggregation of layered double hydroxide nanoparticles in the presence of heparin: towards highly stable delivery systems. Issue 20 (9th February 2016) - Pavlovic, Marko; Li, Li; Dits, Francois; Gu, Zi; Adok-Sipiczki, Monika; Szilagyi, Istvan
Abstract : Heparin coating significantly enhanced the colloidal stability of layered double hydroxide nanoparticles. Abstract : The effect of heparin adsorption on the colloidal stability of layered double hydroxide particles as potential drug delivery agents was studied in aqueous suspensions. The lamellar structures were prepared by the co-precipitation method and composed of magnesium(ii ) and aluminium(iii ) mixed hydroxide as the layers and carbonate anions between the layers. Stable and positively charged particles were observed at low heparin concentrations and low ionic strengths where the surface charge was only partially neutralized by the oppositely charged natural polyelectrolyte adsorbed on the surface. Increasing the heparin dose resulted in charge neutralization and subsequent charge reversal at appropriate doses. The particles aggregated rapidly in the absence of sufficient surface charge, however, remarkably stable dispersions were obtained when the particles were completely covered by heparin. The latter coating process gave rise to two-times higher surface charge density in magnitude and about 20-times higher critical coagulation concentration than for the bare particles. The significant stabilization effect due to the heparin-coating resulted from repulsive interparticle forces of electrostatic and steric origin. On the basis of these findings, efficient delivery systems can be designed where the colloid stability of the carrier particles is enhanced by coating with a biocompatible polyelectrolyte.